Immediate Tight Sealing of Skin Incisions Using an Innovative Temperature-controlled Laser Soldering Device: In Vivo Study in Porcine Skin - Simhon, David (2007)
BACKGROUND: A feedback temperature-controlled laser soldering system (TCLS) was used for bonding skin incisions on the backs of pigs. The study was aimed: 1) to characterize the optimal soldering parameters, and 2) to compare the immediate and long-term wound healing outcomes with other wound closure modalities. MATERIALS AND METHODS: A TCLS was used to bond the approximated wound margins of skin incisions on porcine backs. The reparative outcomes were evaluated macroscopically, microscopically, and immunohistochemically. RESULTS: The optimal soldering temperature was found to be 65°C and the operating time was significantly shorter than with suturing. The immediate tight sealing of the wound by the TCLS contributed to rapid, high quality wound healing in comparison to Dermabond or Histoacryl cyanoacrylate glues or standard suturing. CONCLUSIONS: TCLS of incisions in porcine skin has numerous advantages, including rapid procedure and high quality reparative outcomes, over the common standard wound closure procedures. Further studies with a variety of skin lesions are needed before advocating this technique for clinical use.